Preliminary Study on Gas Storage Capacity and Gas-in-Place for CBM Potential in Balingian Coalfield, Sarawak Malaysia - Sonny Irawan, Sonny (Centre for promoting ideas, USA, 2011)
This project focuses on Coal Bed Methane (CBM) potential in Balingian coalfield, Sarawak. One block in Balingian area is picked as an area for preliminary assessment. Liang formation (Balingian Coal) is lignite coal with a mean vitrinite reflectance of 0.32%, coal seam thickness from 0.33- 29.69 ft. According to Geoscience and Mineral Department Malaysia, the moisture content is in between 12.9% to 18.7%, volatile matter varies at 37.8% to 43.4% with fixed carbon ranges from 40.3% to 43.4%. The coal contains a very low ash content of 2.7% and sulphur content less than 1%. Four different core samples were used with porosity and permeability values from 1.58% to 5.12% and 0.15mD to 46.15mD. Gas storage capacity at different pressures was determined from adsorption isotherm test based on modified Boyle’s law. Adsorption isotherm test result showed maximum adsorbed methane in coal is 374.62scf/ton at maximum pressure of 1219.58 psia. Linear regression of Langmuir Volume and Langmuir Volume showed 714.29scf/ton and 1024.5psia respectively. Value of maximum absorbed methane used in gas-in-place calculation yields 15.207 Bscf in area of 6.094km2. The result is compared with other similar coal fields. As a conclusion, Balingian coal field showed a very good prospect to produce first CBM in Malaysia based on this study